2011
DOI: 10.1128/jcm.02530-10
|View full text |Cite
|
Sign up to set email alerts
|

pO157_Sal, a Novel Conjugative Plasmid Detected in Outbreak Isolates of Escherichia coli O157:H7

Abstract: In addition to the large virulence plasmid pO157, a novel 38-kb conjugative plasmid, pO157_Sal, was identified and sequenced from an Escherichia coli O157:H7 outbreak-associated Chinese isolate that shares high similarity with a plasmid in Salmonella enterica serovar Agona. The plasmid was found in 15 of 326 isolates, 12 of which were of the same pulsed-field gel electrophoresis type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…There are several reports associated with outbreaks of STEC around the world. In a massive outbreak in China, 195 hospitalised HUS patients and 177 deaths have been reported (Wang et al, 2011;Xiong et al, 2012). In another outbreak caused by non-O157 STEC, infected cases including 43 deaths have been recently reported in the European Union (ECDC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports associated with outbreaks of STEC around the world. In a massive outbreak in China, 195 hospitalised HUS patients and 177 deaths have been reported (Wang et al, 2011;Xiong et al, 2012). In another outbreak caused by non-O157 STEC, infected cases including 43 deaths have been recently reported in the European Union (ECDC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The novel plasmid pO157_Sal in Xuzhou21 has been reported previously by our group [24], and this plasmid was only observed in ST96, ST23 and ST98 strains [24]. pO157_Sal contains no known virulence genes [24].…”
Section: Resultsmentioning
confidence: 67%
“…pO157_Sal contains no known virulence genes [24]. Interestingly, a similar plasmid (pEC4115) has also been found in EC4115 [22].…”
Section: Resultsmentioning
confidence: 94%
“…It directly transports toxigenic proteins, but also mediates transportation at the genetic level via bacterial binding, transmits toxigenic genes, enhances pathogen virulence and contributes to bacterial evolution (17)(18)(19)(20). In previous studies, a novel subtype of T4SS known as the type IVC secretion system has been observed (17,20).…”
Section: Discussionmentioning
confidence: 99%